Pengembangan Aplikasi Android Tentang Hubungan Perencanan Karir dan Mata Kuliah (Studi Kasus STMIK Insan Pembangunan) - Haryanto, Budi; Budiadnyana, Gusti Nyoman (Jurnal Informatika Universitas Pamulang, 2021)
The large number of prospective college students and new college students who do not know the relationship between courses and the skills needed in the world of work, causes college students to study at a minimum. Many college students also do not know the relationship between courses and courses that will be taken in the future, making students passive and unprepared when taking courses. There are also students who even just found out that they took the wrong major. This study is intended to provide an overview for prospective students and early students to find out the relationship between courses and careers in the world of work. It is hoped that the final results of this research will be able to provide direction for students to be more serious when taking courses and find out the skills that must be mastered in facing the challenges of the world of work according to their interests and desired career. the other result is to reduce students who drop out in the middle of the road because they do not know the importance of education to build a career.